APPLYING ATTITUDE MAHMUDAH (COMMENDABLE MORAL) TO STUDENTS THROUGH THE LEARNING OF AQIDAH AKHLAK - Farkhan Fuady; Sri Ayu Ratnasari (Yayasan Hurriah, Banda Aceh, 2022)
Learning aqidah morals obtained by students in general and Muslims in general will be useful for creating superior human beings. This is the mandate of the 1945 Constitution. Looking at the current developments, juvenile delinquency often occurs, such as brawls and so on. As an educated person, it is proper to do good and leave bad deeds. Here the role of learning aqidah morals by instilling commendable morals in students. This article aims to explore the concept of commendable morals in the learning of moral aqidah and its application in everyday life. The research method used is a qualitative method with a library research approach. Research data is sourced from various library data such as books, scientific articles, manuscripts and so on. The results of the study show that commendable morals will produce people who are pious to Allah SWT and have an attitude of obedience to Allah SWT. In its application, commendable morals are influenced by oneself, family, teachers, and the environment around the place of residence.